Genes of the GadX-GadW Regulon in Escherichia coli - Tucker, Don L. (American Society for Microbiology, 2003)
Acid in the stomach is thought to be a barrier to bacterial colonization of the intestine. Escherichia coli, however, has three systems for acid resistance, which overcome this barrier. The most effective of these systems is dependent on transport and decarboxylation of glutamate. GadX regulates two genes that encode isoforms of glutamate decarboxylase critical to this system, but additional genes associated with the glutamate-dependent acid resistance system remained to be identified. The gadX gene and a second downstream araC-like transcription factor gene, gadW, were mutated separately and in combination, and the gene expression profiles of the mutants were compared to those of the wild-type strain grown in neutral and acidified media under conditions favoring induction of glutamate-dependent acid resistance. Cluster and principal-component analyses identified 15 GadX-regulated, acid-inducible genes. Reverse transcriptase mapping demonstrated that these genes are organized in 10 operons. Analysis of the strain lacking GadX but possessing GadW confirmed that GadX is a transcriptional activator under acidic growth conditions. Analysis of the strain lacking GadW but possessing GadX indicated that GadW exerts negative control over three GadX target genes. The strain lacking both GadX and GadW was defective in acid induction of most but not all GadX target genes, consistent with the roles of GadW as an inhibitor of GadX-dependent activation of some genes and an activator of other genes. Resistance to acid was decreased under certain conditions in a gadX mutant and even more so by combined mutation of gadX and gadW. However, there was no defect in colonization of the streptomycin-treated mouse model by the gadX mutant in competition with the wild type, and the gadX gadW mutant was a better colonizer than the wild type. Thus, E. coli colonization of the mouse does not appear to require glutamate-dependent acid resistance.